Prospects of the Construction Industry in Uzbekistan and Issues of Improving the Audit System in It (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the issues of conducting audits at enterprises operating in the construction sector of our country. At the same time, the stages of inspections at construction enterprises were analyzed and proposals were made to improve the industry.